Application of the Milan System for Reporting Salivary Gland Cytopathology: A Tertiary Care Experience - Anjaria, Jheel Sureshbhai; Patel, Purvi Sharad; Vaghasiya, Shital P.; Hadavani, Dipal Kantibhai; Rajmohan , Sree Pooja; Goswami , Hansa (Annals of Pathology and Laboratory Medicine, 2025)
Background: Fine-needle aspiration cytology (FNAC) of salivary gland lesions poses diagnostic challenges due to diverse features and overlapping characteristics. To address this, the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) was established to promote standardized reporting and improve clinico-pathologic correlation. The aim of the present study was to assess the application of the MSRSGC on FNAC specimens of salivary gland lesions at B.J. Medical College and Hospital. Materials and Methods: A retrospective study was conducted, retrieving clinical information and cytology smear slides from salivary gland lesions diagnosed between January 2022 and July 2024. The cytological features were evaluated and the cases were classified according to the MSRSGC. Results: A total of 118 cases were evaluated cytologically. The distribution of cases into different categories was as follows: Non-diagnostic (12.71%), Non-neoplastic (38.99%), Atypia of Undetermined Significance (5.08%), Neoplasm: Benign (33.05%), Salivary Gland Neoplasm of Uncertain Malignant Potential (3.39%), Suspicious for Malignancy (1.69%), and Malignancy (5.08%). The Risk of Malignancy (ROM) for non-diagnostic, non-neoplastic, benign neoplasms, AUS, SUMP, SFM, and malignant were 0%, 0%, 50%, 2.7%, 100%, 100%, and 100%, respectively. Conclusion: The MSRSGC is an essential tool for standardizing reporting and preoperatively stratifying cases. The findings of this study reinforce the value of MSRSGC in enhancing diagnostic accuracy, stratifying malignancy risk, and facilitating collaborative patient management between cytopathologists and clinicians, highlighting the need for ongoing refinement and widespread adoption.